Logistical model to approximate the S Curve of the planning of sewage projects (Gaceta Técnica, 2019)
The engineering projects have a plan of activities to be carried out in an estimated initial time, which is contrasted with the real time that the execution of the project took. This initial plan is of utmost importance for both the builder and the contracting entity of the work, since this represents a direct relationship of the costs of each stage and the time they demand. The graphic representation of this relationship is adopted as a planning resource, and its form is similar to the S curve. On this graph, it can be seen that at the beginning of the project the accumulated costs are increasing, and at the end of the project it is observed that they decrease. For these reasons, this paper presents a logistic equation model that predicts the planning of a sewer construction project based on a given budget for its execution and the estimated initial time. The model is constructed from a representative sample of sewerage projects executed in the province of Pichincha, and is validated using other that not taken into account in said sample. The model proposed in this paper has as an added value its usefulness in decision-making by public entities because it provides a more accurate estimate of the project's valued timeline
Keywords: S curve; logistic equation; construction projects planning; control of works